2011
DOI: 10.1080/10508422.2011.585601
|View full text |Cite
|
Sign up to set email alerts
|

Do Undergraduate Student Research Participants Read Psychological Research Consent Forms? Examining Memory Effects, Condition Effects, and Individual Differences

Abstract: While research has examined factors influencing understanding of informed consent in biomedical and forensic research, less is known about participants’ attention to details in consent documents in psychological survey research. The present study used a randomized experimental design and found the majority of participants were unable to recall information from the consent form in both in-person and online formats. Participants were also relatively poor at recognizing important aspects of the consent form inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
3
26
1
Order By: Relevance
“…In early analysis, it was found that only 14% of participants were able to recall the essential elements of consent, including potential risks from sharing personally identifiable genetic data and amount of monetary compensation offered for participation. A more recent examination of research participant comprehension of informed consent documents demonstrated similarly low rates of comprehension, ranging between 11% and 31% comprehension across a variety of informed consent points (Pedersen et al, 2011).…”
Section: Comprehension In Informed Consent Researchmentioning
confidence: 97%
See 4 more Smart Citations
“…In early analysis, it was found that only 14% of participants were able to recall the essential elements of consent, including potential risks from sharing personally identifiable genetic data and amount of monetary compensation offered for participation. A more recent examination of research participant comprehension of informed consent documents demonstrated similarly low rates of comprehension, ranging between 11% and 31% comprehension across a variety of informed consent points (Pedersen et al, 2011).…”
Section: Comprehension In Informed Consent Researchmentioning
confidence: 97%
“…Further, this study is framed around behavioral genetic research to further the understanding of what methods are most effective for communicating information relevant to the informed consent process in this emerging and ethically challenging domain of behavioral genetic research. As an additional feature, this study examines comprehension of informed consent documents for behavioral genetic research immediately following the presentation of the information using cued recall measurements from previous literature (Ascheman, 2009;Pedersen et al, 2011;Batchelder 2012) as well as cued recall and recognition measurements one week after initial presentation. This approach provides additional insight regarding how well information regarding elements of informed consent is retained for behavioral genetic studies after a significant delay, which is particularly relevant as digitized genetic information may be stored and potentially used in future analyses as new technologies and methodologies emerge.…”
Section: Purpose Of Studymentioning
confidence: 99%
See 3 more Smart Citations